Multiple anomalies in the atlanto-occipital joint (articulation atlanto-occipitalis) - Mańkowska-Pliszka, Hanna; Wieczorek, Urszula; Wysocki, Jarosław; Tomczyk, Jacek (Anthropological Review, 2013)
Contemporary populations exhibit numerous skeletal anatomical variations and the atlanto-occipital joint (articulation atlanto-occipitalis) is often the location of such variations. A female skeleton dated at 4000 BC and excavated at Meroe in the Sudan provides an example of numerous variations in the basilar skull and cervical vertebrae. These variations consist of the presence of a bilateral atlanto-occipital joint with a third trochanter, a unilateral arcuate atlas foramen and huge axial nutrient foramina.